Inhibition of Major Histocompatibility Complex II Expression and Antigen Processing in Murine Alveolar Macrophages by Mycobacterium bovis BCG and the 19-Kilodalton Mycobacterial Lipoprotein - Fulton, Scott A. (American Society for Microbiology, 2004)
Alveolar macrophages constitute a primary defense against Mycobacterium tuberculosis, but they are unable to control M. tuberculosis without acquired T-cell immunity. This study determined the antigen-presenting cell function of murine alveolar macrophages and the ability of the model mycobacterium, Mycobacterium bovis BCG, to modulate it. The majority (80 to 85%) of alveolar macrophages expressed both CD80 (B7.1) and CD11c, and 20 to 30% coexpressed major histocompatibility complex II (MHC-II). Gamma interferon (IFN-γ) enhanced MHC-II but not B7.1 expression. Naive or IFN-γ-treated alveolar macrophages did not express CD86 (B7.2), CD11b, Mac-3, CD40, or F4/80. M. bovis BCG and the 19-kDa mycobacterial lipoprotein inhibited IFN-γ-regulated MHC-II expression on alveolar macrophages, and inhibition was dependent on Toll-like receptor 2. The inhibition of MHC-II expression by the 19-kDa lipoprotein was associated with decreased presentation of soluble antigen to T cells. Thus, susceptibility to tuberculosis may result from the ability of mycobacteria to interfere with MHC-II expression and antigen presentation by alveolar macrophages.